THEORETICAL AND METHODOLOGICAL BASES OF THE ANALYSIS OF GLOBAL STRATEGY OF THE VERTICALLY INTEGRATED OIL COMPANIES - E. Makhankov (Publishing House of the State University of Management, 2016)
In the article the main theoretical questions of formation of global strategy of the oil companies are generalized. The indirect and direct factors influencing these strategy are revealed. Role of scientific and technical progress and innovations in the external economic strategy of the vertically integrated oil companies is specified.